Analysis of The Factors That Influence The Perceptions of Culinary Business Owners Regarding Intention to Register For Halal Certificates: Analisis Faktor-Faktor Yang Mempengaruhi Persepsi Pemilik Usaha Kuliner Tentang Niat Mendaftar Sertifikat Halal - Priantina , Anita; Indra, Indra; Zaerofi, Afif; Mughni, Abdul (Perisai : Islamic Banking and Finance Journal, 2023)
Indonesia Law No. 33 of 2014 concerning Halal Assurance requires that by 2019 halal certification should be effectively implemented for food and beverage products, as well as service products related to both. Out of the 1.6 million micro, small, and medium enterprises (MSMEs), only 10 percent have been halal certified. This study aims to analyze the factors that influence the perceptions of culinary business owners regarding intention to register for halal certificates. Theory of Planned Behavior will be modified and implemented in preparing the frameworks of the dependent-independent variables. Using partial least square method, 200 sample of culinary producers -owners and managers- in Bogor were studied. Intention of producers is found to be significantly influenced by trust. Trust is also found to be sensitive to functional factor and subjective norm. Trust is also found to be determining attitude, together with functional factor and perceived behavioral norms. Trust is also significant in mediating the effect of perceived behavioral norms to intention, and also in mediating the effect of subjective norm to intention.The population of this study is the MSMEs culinary producers in Great Bogor Area, West Java, Indonesia. Only the respective owners and managers of the responding businesses were the main respondent. Similar research should be done for other types of halal product in order to generalize the results.This research modify TPB in setting the framework of determinants for halal certification intention. Variables added to the original TPB framework are trust and functional factor.This result concludes that trust is crucial in the effort to increase the number of halal certified products in Bogor. The halal certification authorities would have basis to review their policies, procedures, and technical guidelines for halal certification process. This study could be extended in terms of object and other potential determinant variables. Literatures related to halal certification has limited exposure to producers’ motivation for halal certification